Safety issues at partially abandoned commercial buildings in Setia Taipan, Shah Alam / Adzaty Lyana Adam - Adzaty Lyana, Adam (2020)
The safety of a development is important to prevent unwanted things from happening in the area. Lack of street lights, adequate signage and prominence and attractive landscapes can lead to unintended crime. For example, cases of rape, robbery and road accidents. This situation causes the emergence of an awareness of the dangers of these abandoned commercial and need to enhance the deficiency to not give trouble in human daily activities. This research aim is to study the attraction and safety on the commercial area in Setia Taipan, Shah Alam. This research is based on data obtained from survey questionnaire that related to landscape issues, street lights and safety issues. The data was analysed to evaluate and determined the safety issues and its level of preferences to be a safety and vibrant commercial. This research is written generally about the problems of the commercial area that found in Setia Taipan, Shah Alam and search the elements that makes the commercial area out of the public to end of this research proposal. The result of the study also suggested that successful, vibrant and safe commercial area is needed for the local authority to successfully managing the commercial area. It is hope that the study can contribute to the improvement of the commercial area.